Religious Education and non-affiliation in Belgium and in Germany: Roman-Catholic and Protestant Evangelical Perspectives - Franken, Leni (Theo-Web, 2021)
Based on the EKD report Religiöse Bildung ansgesichts von Kofessionslosigkeit as well as on the new curriculum for Roman Catholic RE in the Flemish Community (Belgium), the recent recommendations concerning Protestant-Evangelical RE in Germany will be compared with the recent developments in Roman-Catholic RE in Flanders. A brief sociological sketch makes clear that in both contexts, an increasing number of students enrolled in RE are non-affiliated. Taking this into consideration, I will scrutinize how the Roman Catholic Church in Belgium (Flemish Community) as well as the EKD responded to this new societal situation. To conclude, the new developments in RE in both contexts will be briefly evaluated and suggestions for further comparative research will be made.